2002
DOI: 10.1002/nbm.723
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivity of two adenocarcinoma xenografts to the anti‐vascular drugs combretastatin A4 phosphate and 5,6‐dimethylxanthenone‐4‐acetic acid, assessed using MRI and MRS

Abstract: The effects of two anti-vascular agents, combretastatin A4 phosphate (CA4P), and 5,6-dimethylxanthenone-4-acetic acid (DMXAA), on the perfusion of two human colon adenocarcinomas implanted in SCID mice, were assessed for up to 3 h using non-invasive magnetic resonance imaging (MRI) and spectroscopy techniques (MRS). MRI measurements of GdDTPA inflow showed that treatment with CA4P had little effect on the perfusion of HT29 tumours. Localized 31 P MRS measurements also showed that the drug had no significant ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 14 publications
1
42
0
Order By: Relevance
“…The results reported here show the potential of using DCE-MRI in ZD6126 dose-finding studies in humans. Although a number of studies have already shown the potential of using DCE-MRI with the vascular-targeting agents CA4P (7,(13)(14)(15)(21)(22)(23) and DMXAA (22,24), there is only one published study for ZD6126 (25). In addition, we have shown that ZD6126 dosedependent changes can be measured using MRI and that the approach developed in murine tumors can be translated into the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The results reported here show the potential of using DCE-MRI in ZD6126 dose-finding studies in humans. Although a number of studies have already shown the potential of using DCE-MRI with the vascular-targeting agents CA4P (7,(13)(14)(15)(21)(22)(23) and DMXAA (22,24), there is only one published study for ZD6126 (25). In addition, we have shown that ZD6126 dosedependent changes can be measured using MRI and that the approach developed in murine tumors can be translated into the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed acute hypoxiation within 90 mins following CA4P administration to rats bearing syngeneic breast 13762NF tumors using MRI (30). Rapid vascular shut-down in tumors after administration of CA4P to animals and patients has also been observed by many other imaging modalities including positron emission tomography (PET) based on the distribution of 15 O water (31), DCE MRI (24,32,33), DCE computed tomography (CT) (34), 19 F MRI of tumor oxygenation (30), Laser Doppler flowmetry (35), radiolabeled iodoantipyrine (IAP) uptake (27), near infrared spectroscopy (36), interstitial fluid pressure (IFP) (35) and intra vital microscopy (37). By comparison bioluminescence imaging is particularly inexpensive and easy to apply in animal models and we believe it could be an effective screening tool for evaluation and comparison of vascular targeting agents as well as long-term tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is one approach that affords such biomarkers of response to antivascular therapies, and drug efficacy has been demonstrated in both preclinical (Beauregard et al, 2002;Maxwell et al, 2002) and clinical studies (Dowlati et al, 2002;Galbraith et al, 2002). In this study, we describe the use of two MRI techniques for the noninvasive assessment of the dose-dependent antivascular activity of ZD6126 on tumour perfusion.…”
mentioning
confidence: 99%